Numerical simulation of a viscoelastic sound absorbent coating with a doubly periodic array of cavities. Issue 1 (1st January 2018) - Sohrabi, Sayed Hamid; Ketabdari, Mohammad Javad
Abstract: Nowadays, research on underwater sound absorbing coatings is important on marine combats. Due to high cost of acoustic experimental tests, determination of an accurate simulation method for assessment of the coating characteristics is an important goal for scientists. In this paper, a simulation-based code in ANSYS was developed. Embedding cavities in coating mediums is a way to improve their acoustic performance. The behavior of a sound absorption coating dramatically depends on the medium features, layer thickness, the size and distribution of cavities. Due to cavities symmetrical distribution and calculating time reduction and cost, only one isolated unit cell of a periodic sound absorption coating was studied. In this study, two fluid mediums in front and back of coating are modeled. The objective is to study the acoustic performance of the absorbent coating due to normal incident plane wave. The present model results were compared with measurements test data. The good agreement in this comparison illustrates the accuracy and validity of the model. The model was then utilized to investigate the effects of cavity geometry on the behavior of sound absorption coatings. The results of the comparison between a cone frustum hole and a cylindrical hole demonstrate larger transmission coefficients in cone frustum holes. Echo reduction results show no major difference between these coatings with the above mentioned types of holes. Furthermore, it is evident from the results that in general, in low-frequency ranges under 10 kHz, material characteristics play the most important role regarding sound absorption and dissipation properties.